Treatment of Epidermolysis Bullosa and Future Directions: A Review - Sorina Danescu; Mircea Negrutiu; Cristina Has (Adis, Springer Healthcare, 2024)
Abstract Epidermolysis bullosa (EB) comprises rare genetic disorders characterized by skin and mucosal membrane blistering induced by mechanical trauma. Molecularly, pathogenic variants affect genes encoding proteins crucial for epidermal-dermal adhesion and stability. Management of severe EB is multidisciplinary, focusing on wound healing support, ensuring that patients thrive, and complication treatment. Despite extensive research over 30 years, novel therapeutic approaches face challenges. Gene therapy and protein therapy struggle with efficacy, while regenerative cell-based therapies show limited effects. Drug repurposing to target various pathogenic mechanisms has gained attention, as has in vivo gene therapy with drugs for dystrophic and junctional EB that were recently approved by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA). However, their high cost limits global accessibility. This review examines therapeutic advancements made over the past 5 years, exploiting a systematic literature review and clinical trial data.